IDENTIFICATION OF INNOVATION PROCESS ON NEW PRODUCT DEVELOPMENT IN SMALL AND MEDIUM ENTERPRISES - Efrata, Tommy C.; Radianto, Wirawan E.D; Marlina, Maria A. E. (Universitas Brawijaya, Indonesia, 2019)
Understanding the innovation process of new product development (NPD) is expected to support the company's sustainability. This study aims to identify the NPD innovation process in the food and beverage industry in Indonesia. The research method uses a qualitative multiple case study approach in 4 small and medium scale firms in the food and beverage industry in Indonesia. The results show that the NPD innovation process went through several stages, namely: idea generation, filtering idea, concept development, and testing, marketing development and strategy, business analysis, market testing, and commercialization. The results of this study can be used as a reference for companies on the same scale to innovate new products.